Differences in the Surgical Treatment of Lower Back Pain Among Spine Surgeons in the United States. Issue 11 (June 2016) - Lubelski, Daniel; Williams, Seth K.; O'Rourke, Colin; Obuchowski, Nancy A.; Wang, Jeffrey C.; Steinmetz, Michael P.; Melillo, Alfred J.; Benzel, Edward C.; Modic, Michael T.; Quencer, Robert; Mroz, Thomas E.
Abstract : Study Design: Electronic survey. Objective: To identify the surgical treatment patterns for low back pain (LBP), among U.S. spine surgeons. Specifically determine (1) differences in surgical treatment responses based on various demographic variables; (2) probability of disagreement based on surgeon subgroups. Summary of Background Data: Multiple surgical and nonsurgical treatments exist for LBP. Without strong evidence or clear guidelines for the indications and optimal treatments, there is substantial variability in surgical treatments used. Methods: A total of 445 U.S. spine surgeons completed a survey of clinical and radiographic case scenarios on patients with mechanical LBP, no leg pain, and concordant discograms. Surgical treatment options included no surgery, anterior lumbar interbody fusion (ALIF), posterolateral fusion with pedicle screws, transforaminal/posterior lumbar interbody fusion (TLIF/PLIF), etc . Statistical significance was set at 0.01 to account for multiple comparisons. Results: There was substantial clinical equipoise (∼75% disagreement) among surgeons on the approach to treat patients with LBP. Disagreement was highest in the southwest and lowest in the Midwest (82% vs. 69%, respectively); there was significantly lower disagreement among those in academic practices versus those in private/hybrid practices (56% vs. 79%, respectively). Those in academic practices had approximately four times greater odds of choosing no surgery as compared to those in hybrid and private practices, who were more likely to choose ALIF or PLIF/TLIF. Those with fellowship training had approximately two times greater odds of selecting no surgery and four times greater odds of selecting ALIF as compared to those without fellowship training who were more likely to select TLIF/PLIF. Conclusion: Significant differences exist among U.S. spine surgeons in the treatment of LBP. These differences stem from geographical location of the practice, specialty, practice type, and fellowship training. Recognizing the substantial variability underlies the importance of additional studies aimed at identifying the proper indications and most cost-effective treatments for LBP. Level of Evidence: 3